Overexpression of TaWRKY146 Increases Drought Tolerance through Inducing Stomatal Closure in Arabidopsis thaliana - Ma, Jianhui; Gao, Xiaolong; Liu, Qing; Shao, Yun; Zhang, Daijing; Jiang, Lina; Li, Chunxi (Frontiers in Plant Science, 2017)
As a superfamily of transcription factors, the WRKY transcription factors have been found to be essential for abiotic and biotic stress responses in plants. Currently, only 76 WRKY transcription factors in wheat could be identified in the NCBI database, among which only a few have been functionally analyzed. Herein, a total of 188 WRKY transcription factors were identified from the wheat genome database, which included 123 full-length coding sequences, and all of them were used for detailed evolution studies. By bioinformatics analysis, a WRKY transcription factor, named TaWRKY146, was found to be the homologous gene of AtWRKY46, overexpression of which leads to hypersensitivity to drought and salt stress in Arabidopsis. Consequently, the full length of TaWRKY146 was cloned, and the expression levels of TaWRKY146 were found significantly up-regulated in the leaves and roots of wheat seedlings, which were subjected to osmotic stress. Overexpression of TaWRKY146 in Arabidopsis was shown to enhance drought tolerance by the induction of stomatal closure that reduced the transpiration rate. All these results provide a firm foundation for further identification of WRKY transcription factors with important functions in wheat.